2018
DOI: 10.30590/vol5-no1-p1-11
|View full text |Cite
|
Sign up to set email alerts
|

Sugar, Salt and Fat Consumption of Population in Batur Kidul Village Getasan Subdistrict Semarang Regency

Abstract: The prevalence of non-contagious diseases such as diabetes mellitus, hypertension and obesity are increasing from year to year. Unhealthy diet such as excessive consumption of sugar, salt and fat is one of the factors causing these diseases. The result of data analysis shown that 21.5% of respondents had consumed sugar exceeding the recommendation of Permenkes no 30 year 2013 (>50 gram/day), 73.7% of respondents consume salt exceeding the recommendation of Permenkes no 30 year 2013 (5 gram/day), and as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“… 1 The Indonesian Food Composition Table 2005 [ 11 ]; the USDA National Nutrient Database for Standard Reference 2015 [ 12 ]; the Food Composition Table of Singapore [ 13 ]; 2 commercial products enlisted by the National Agency for Drug and Food Control—Indonesia. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… 1 The Indonesian Food Composition Table 2005 [ 11 ]; the USDA National Nutrient Database for Standard Reference 2015 [ 12 ]; the Food Composition Table of Singapore [ 13 ]; 2 commercial products enlisted by the National Agency for Drug and Food Control—Indonesia. …”
Section: Figurementioning
confidence: 99%
“…These efforts can be started by evaluating the consumption level in certain populations. Studies on the total added sugar, salt, and fat intakes in Indonesia had been reported by several research groups [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, information regarding the contribution of food sources/origin (homemade, processed or street/restaurant/fast foods) to the daily food consumption, including sugar, salt, and fat intakes, has not previously been reported in the Indonesian population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mostly examined the consumption of sugar, salt, and fat. Such as research on the description of sugar, salt, and fat consumption in the region (Triandhini, Rahardjo, & Putranti, 2018) and research on the description of sugar, salt, and fat consumption in children (Rembet, Nugroho, & Mangalik, 2021). The study mentioned that excessive consumption of sugar, salt, and fat is the cause of noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%